2017
DOI: 10.1063/1.4968308
|View full text |Cite
|
Sign up to set email alerts
|

The use of sugarcane bagasse in PP matrix composites: A comparative study of bagasse treatment using calcium hydroxide and sodium hydroxide on composite strength

Abstract: Fabrication of mesoporous silica nanoparticles by sol gel method followed various hydrothermal temperature AIP Conference Proceedings 1945, 020052 (2018) Abstract. Sugarcane fibers have been studied as reinforcement fibers to develop biocomposites of sugarcane fiberspolypropylene (PP). In this study, two different alkaline solutions were used to modify the sugarcane bagasse fibers, i.e. 10% v/v NaOH and 14% v/v Ca(OH)2 solution for 4 hours. Sugarcane fibers filled to polypropylene (PP) matrix was 3 cm, 5 cm an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
1
9
0
1
Order By: Relevance
“…PP using both treated fibers and the results have been reported elsewhere [31]. Overall the strength of the composites using the Ca(OH)2 treated fibers was lower than the strength obtained using NaOH treated bagasse fibers.…”
supporting
confidence: 69%
“…PP using both treated fibers and the results have been reported elsewhere [31]. Overall the strength of the composites using the Ca(OH)2 treated fibers was lower than the strength obtained using NaOH treated bagasse fibers.…”
supporting
confidence: 69%
“…Anggono et al [ 19 ] studied the incorporation of bagasse (up to 30 wt.%) in a polypropylene (PP) matrix using injection molding processes. They perform alkali treatments on the fibers with calcium hydroxide (Ca(OH) 2 ) and sodium hydroxide (NaOH) and evaluated the effect of those treatments on the mechanical properties of the biocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…8,10,11 Although HDPE is a safe plastic material owing to its chemical resistance with packaged food or beverages, it is not recommended to be used repeatedly due to the increasing release of antimony trioxide compounds with time. 10 Good numbers of research articles are published related to PE bagasse 1,7,12,13 and PP bagasse 3,5,14,15 composites. Agunsoye and Aigbodion have carried out the investigation on the uncarbonized bagasse (UB) and carbonized bagasse (CB) particles (10–50 wt%) filled with recycled PE biocomposites, and their results showed that the increase of tensile and bending strength achieved the maximum extent at 20 wt% UB and 30 wt% CB.…”
Section: Introductionmentioning
confidence: 99%